The red tide event in El Salvador, August 2001-January 2002 - Barraza, José Enrique (2004)
A red tide event occurred in El Salvador from August 2001 to January 2002. National health authorities usually measured toxin levels in Ostrea iridescens, however other species were analyzed during this microalgae bloom: Anadara similis, Anadara tuberculosa and Modiolus sp. El Salvador authorities consider 400 mouse units/100 g the highest value that is safe for human health. During this period toxin levels in O. iridescens and Modiolus sp. increased from values under 400 to 3 977 and 15 468 mouse units/100 g, respectively. Persistent and higher levels were recorded in oyster and mussel banks on the west part of the country. The Ministry of Health and Social Assistance treated 41 slight to moderate intoxications associated to bivalve mollusks consumption.A red tide event occurred in El Salvador from August 2001 to January 2002. National health authorities usually measured toxin levels in Ostrea iridescens, however other species were analyzed during this microalgae bloom: Anadara similis, Anadara tuberculosa and Modiolussp. El Salvador authorities consider 400 mouse units/100 g the highest value that is safe for human health. During this period toxin levels in O. iridescens and Modiolus sp. increased from values under 400 to 3 977 and 15 468 mouse units/100 g, respectively. Persistent and higher levels were recorded in oyster and mussel banks on the west part of the country. The Ministry of Health and Social Assistance treated 41 slight to moderate intoxications associated to bivalve mollusks consumption.